Impact of facemasks on the mouth as an emerging dental concern: A survey among residents of Karachi - Muhammad Muzzamil; Hana Pervez; Rimsha Nawaz; Shaeroz Raza; Zoaib Habib Tharwani; Maryam Nisa (Elsevier, 2023)
Background: The illness known as ''mask-mouth syndrome,'' which is brought on by constantly covering one's mouth and nose with a mask, was particularly prevalent among healthcare personnel. The covid-19 pandemic, however, had far-reaching effects on people's daily lives all around the world, to the point where mask use became practically mandatory. With Covid-19 posing a new threat to dental health, this study aims to assess the public's awareness of the issue and investigate how wearing a facemask affects oral hygiene. Methods: Cross-sectional research was conducted at Karachi's Jinnah Medical & Dental College. From February to May of 2022, it was carried out in the Dental Opd. A survey of 400 people was conducted, representing a cross-section of society in terms of age, gender, occupation, and other criteria. The poll had 11 closed-ended questions. The data was analyzed using SPSS 24. Descriptive analysis was used to examine the responses. Results: Men made up 44.5% (n = 174) of responses and women 56.5% (n = 226). Mean participant age was 27.31, ranging from 18 to 50. 99% (n = 396) of respondents wear masks. 48% (n = 192) of participants were uncomfortable using facemasks. Disposable face masks were voted the best option by 60.5% of respondents (n = 242). Negative effects or conditions brought on by mask use, such as halitosis (47.3%, n = 189) and dehydration (64.3%, n = 257). Conclusion: Mask-mouth syndrome can occur as a result of using a face mask for prolonged periods of time. Mask benefits outweigh the danger of mask mouth syndrome.